2014
DOI: 10.1371/journal.pone.0085756
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Influences of the Medial Olivocochlear Efferent System in Speech Perception in Noise

Abstract: One of the putative functions of the medial olivocochlear (MOC) system is to enhance signal detection in noise. The objective of this study was to elucidate the role of the MOC system in speech perception in noise. In normal-hearing human listeners, we examined (1) the association between magnitude of MOC inhibition and speech-in-noise performance, and (2) the association between MOC inhibition and the amount of contralateral acoustic stimulation (CAS)-induced shift in speech-in-noise acuity. MOC reflex measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 45 publications
7
83
2
6
Order By: Relevance
“…The simulations demonstrated that the amount of this gain inhibition is frequency-dependent with a maximal effect (at the range of 8 to 11 dB) for frquencies between 1 and 3.5 kHz. This was shown to reasonablly agree with the experimental data recorded from guinea pig, cat and human cochleae [1,5,7] where the MOC efferents had been externally elicited by broad-band stimuli.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The simulations demonstrated that the amount of this gain inhibition is frequency-dependent with a maximal effect (at the range of 8 to 11 dB) for frquencies between 1 and 3.5 kHz. This was shown to reasonablly agree with the experimental data recorded from guinea pig, cat and human cochleae [1,5,7] where the MOC efferents had been externally elicited by broad-band stimuli.…”
Section: Resultssupporting
confidence: 81%
“…OAEs are produced in the inner-ear and their level is an important physiological indicator of the underlying OHC gain properties of the cochlea [4]. Their results [7] demonstrated an average 17.21% decrease in the CEOAE level due to the contralateral activation of the MOC efferents, which is comparable with the simulation results here ( Fig. 2A) showing a 19% gain reduction in the middle of the cochlea.…”
Section: Comparison With Experimental and Clinical Datasupporting
confidence: 88%
See 1 more Smart Citation
“…MOC feedback to the cochlea is believed to play roles in deciphering signals such as speech in noisy environments and protecting the cochlea from traumatizing exposures to sound (Liberman et al 2014;Mishra and Lutman 2014). Anomalous MOC function has been hypothesized, and tested for, in a variety of clinical conditions, including tinnitus, a prevalent and often disruptive condition in which sound is perceived in the absence of actual sound (Shargorodsky et al 2010;Stouffer and Tyler 1990).…”
mentioning
confidence: 99%
“…A widely used test of MOC function was employed that measures the effect of sound to one ear on the otoacoustic emissions (OAE) produced by outer hairs cells of the opposite ear (Hood et al 1996;Veuillet et al 1991). When measured in normal human subjects using common protocols, the effect is generally suppressive; that is, the magnitude of the OAE, for instance, distortion-product OAE (DPOAE), is reduced by contralaterally presented sound (commonly broadband noise; Hood et al 1996;Moulin et al 1993). In this study, DPOAE suppression was found in all subject groups, but it was greater in the groups with tinnitus and/or low SLT, indicating increased responsiveness of the MOC system.…”
mentioning
confidence: 99%